Numerical investigation of influence of the design parameters on the operating speed of the electronically controlled injector - Kerimov Z.Kh; Jafarli M.K (Научно-технический вестник Брянского государственного университета)
One of the actual problems of transport energetic is to meet the requirements for both environmental and technical and economic characteristics of automobile engines. Therefore, to meet these requirements, a new working process for the internal combustion engine was proposed and a new design of the electronically controlled injector was developed in accordance with the requirements of the new working process. One of the essential requirements for the developed design of an electronically controlled injector is high operating speed. Therefore, the objective of this work is the implementation of research to improve the operating speed of the injector. By the method of mathematical modeling investigated the influence of various design parameters on the performance and the operating speed of the injector. The results of the numerical investigations are presented and analyzed. As a result, the rational values of the design parameters of the developed electronically controlled injector are determined.